An Analysis of Consumer Decision-Making in Digital Mobile Payment Adoption: Exploring Influencing Factors - Tulkin Kazakov; Mohammad Fakhrul Islam; Belal Mahmoud AlWadi; Muhammad Usman Khan; Md Billal Hossain; László Vasa (Decision Making: Applications in Management and Engineering, 2024)
Despite every one of the upsides of mobile payment services (MPs), they are unutilized by a sizable client base. This paper analyzes the central drivers of utilizing MPs for purchasing purposes from the consumers' point of view in Uzbekistan. Given the Technology Acceptance Model (TAM), the study built up a seven-figure model to uncover the determinants of customers' goals to utilize MPs. 300 respondents in Uzbekistan were selected, and 276 substantial responses were incorporated into the analysis. The structural equation model results applied that customers' goal to utilize MPs for purchasing purposes is impacted by trust, system usefulness, social influence, risk, hedonic motivation, and attitude. The factor, facilitating conditions was not significant interestingly which the most distinct finding of that study is. Considering the findings and discussion, the paper concludes with the notion that mobile payment as a digital innovative financial technology is influenced by most of the factors that mobile operators should look at closely.